Analisis Dan Perancangan Aplikasi Career Center Berbasis Web Dengan Menggunakan Metode Profile Matching - Azhar, Muhammad Rifqi; Puspitarani, Yan (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The primary purpose of vocational education in the Vocational School (SMK) is to prepare students for work. In this respect, the Career Center plays crusial part in providing students with career guidance and job information. A web-based Career Center application is a relevant solution for improving the accessibility and effectiveness of career services in the modern era. In this study, the Career Center with the Macthing Profile method will help students in finding the right job vacancies according to the skills they have. This career center application is built by collecting data, performing computational analysis, and performing system needs analysis. The application uses the Major, Skill and Domisili as criteria, user profiles with ID P01 and P02 as standard values, as well as vacancy codes V01, V02, V03 and V04 as job vacancies used in the Profile Matching process. From the results of the research obtained jobs with vacancial code V01 which has the highest value for User ID P01, and vacant code V04 that has the most value for user ID P02